2011
DOI: 10.3109/00016357.2011.600714
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Ki-67 and p53 protein in ameloblastoma and keratocystic odontogenic tumor

Abstract: The results suggest that the p53 protein expression does not necessarily imply an association with malignant disease and/or p53 gene mutation, but a tendency to be expressed in an increasing quantitative and qualitative manner, as the biologic behavior of odontogenic cyst or tumors becomes more aggressive. p53 over-expression may promote cell proliferation in odontogenic lesions. Thus, it can be stipulated that Ki-67 and p53 protein expression can be used as a prognostic marker in odontogenic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
2
21
1
8
Order By: Relevance
“…Studies comparing the proliferation rate between dentigerous cysts and ameloblastomas have generated conflicted results, which may reflect differences in the markers and criteria used for the cellular proliferation assessment. Gadbail et al found a significantly higher Ki-67 labeling index in ameloblastomas than in dentigerous cysts (46). Also, in another study, Ki-67 expression was observed to be higher in ameloblastomas that arise from dentigerous cysts than in the dentigerous cysts (47).…”
Section: A B C D E F G Hmentioning
confidence: 87%
“…Studies comparing the proliferation rate between dentigerous cysts and ameloblastomas have generated conflicted results, which may reflect differences in the markers and criteria used for the cellular proliferation assessment. Gadbail et al found a significantly higher Ki-67 labeling index in ameloblastomas than in dentigerous cysts (46). Also, in another study, Ki-67 expression was observed to be higher in ameloblastomas that arise from dentigerous cysts than in the dentigerous cysts (47).…”
Section: A B C D E F G Hmentioning
confidence: 87%
“…However, not all cells containing the Ki-67 antigen are actively proliferating cells, and the use of Ki-67 to assess proliferative activity is not advised in tissues over expressing p53 or p21 [28]. It should further be noted that correlation between mitotic and Ki-67 labeling indices is variable [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Os autores concluíram que é possível que o comportamento biológico do TOC pode estar relacionado com a região suprabasal proliferativa no epitélio cístico, observado pelos altos níveis de Ki-67 e p53. Por outro lado, Gadbail et al (12) verificaram uma maior positividade do Ki-67 e do p53 em ameloblastomas do que em TOC. Esses resultados sugerem que o aumento da expressão do p53 não necessariamente implicaria associação apenas com lesões odontogênicas malignas (23) , mas uma tendência de ser expressa em lesões císticas e TOs mais agressivos, podendo promover a proliferação celular nessas lesões (12) .…”
Section: Proliferação Celularunclassified
“…A atividade proliferativa dessas células também tem sido relatada como importante marcador prognóstico e indicador de agressividade biológica. A atividade proliferativa de uma neoplasia vem sendo normalmente avaliada por meio da mensuração da proporção de células comprometidas com o ciclo celular, de modo a avaliar o potencial de crescimento intrínseco da lesão (12) . Em TOs, têm-se investigado a imunolocalização de proteínas do ciclo celular associadas a essas lesões.…”
Section: Introductionunclassified